Офіційне тлумачення Конституції та законів України Конституційним Судом України - Шевчук, Ірина Миколаївна; Shevchuk, I. M. (Ужгородський національний університет, 2012)
У статті досліджено повноваження Конституційного Суду України у сфері тлумачення Конституції і законів України. Проаналізовано поняття, види, суб’єкти та об’єкти тлумачення. Автором визначено правову природу рішень Конституційного Суду України щодо офіційного тлумачення Конституції та законів України.The article deals with the investigation of the powers of the Constitutional Court of Ukraine in the interpretation of the Constitution and the laws of Ukraine. The notion, types, subjects and objects of the interpretation have been analyzed. The legal nature of the decisions of the Constitutional Court of Ukraine as to the legal interpretation of the Constitution and the laws of Ukraine is determined.
Legal interpretation of the constitution and the laws of Ukraine by the constitutional court of Ukraine
Keywords: офіційне тлумачення; нормативне тлумачення; казуальне тлумачення; правова позиція; legal interpretation; normative interpretation; causal interpretation; legal proposition